Effect of Retained Austenite on the Microstructure and Micro-Hardness of AISI 4330 Low Alloy Steel Using X-Ray Diffraction method - Reda, Hadeel K. Abdul; Mohammad, Haider M. (Basrah Journal for Engineering Sciences, 2023)
The mechanical properties of low alloy steel are significantly influenced by retained austenite (RA). Consequently, using the X-Ray diffraction (XRD) measurement method, the retained Austenite volume fractions in AISI4330 alloy steel have been assessed in this article. The specimens underwent heat treatment at various heating temperatures (800 ֯ C, 900 ֯ C,1000 ֯ C) and cooling rates (Water and Oil). The findings demonstrate that retained Austenite formation rises with rising heating (Austenitizing) temperatures for the same quenching media as well as with rising cooling rates. The specimens were heated to a temperature of 1000 °C and then quenched in water, yielding the highest amount of retained austenite (7.733 wt%), and the lowest amount (1.977 wt%), which was obtained when the specimens were heated to a temperature of 800 °C and quenched in oil. The Vickers method was employed to conduct micro-hardness testing, and the results demonstrate that hardness values are reduced as heating temperatures increase. Optical microscopy was used to investigate the effects of retained austenite on the microstructure. The results show that bainite and/or martensite phases with a small amount of retained austenite dominate the microstructure at low cooling rates, whereas martensite and retained austenite phases dominate the microstructure at higher heating and cooling rates.